N enhanced technique for ranking fraud discovery for mobile apps - Abhishek, P; Ravi Kumar, Kallakunta; Naga Bhavya, B (International Journal of Engineering and Technology, 2018)
Now-a-days the mobile applications are very important to the users of android phone for the utilization or to perform different assignments. There are large number of portable application designers are available. Where a few developers make false exercise for making more utilization of their portable application. Due to these duplicate positioning exercises the portable applications enters in the popular application list. The vital point is to raise the avoidance for positioning the duplicate position in portable apps. For this situation huge number of clients makes a fault by downloading the versatile applications which have higher ranking, rating and review. Duplicate ranking indicates the duplicate or unsafe exercises which consists of the reason for bump the apps in popular application list. Utilizing the three confirmations, lastly we are calculating all of those confirmations. Client or user doesn’t have information about the application. So client or user go through the list of the popular applications and downloads or install the applications generally from top page of Application Store. But in some cases it shows that the installed service of application does not work or does not worth. For resolving this duplicity, we make application where we are about to catalogue all the apps which had duplicate ranking. At that point, proposing a process of aggregation which bases on development for combine whole confirmations of the duplicate ranking through the admin and client accounts.
Keywords: Mobile Applications; Duplicate Ranking Detection; Confirmations; Ratings And Reviews.